An Information Systems Study on the International Students Program - Alipio, Ma. Theresa D.; Di, Nerissa C.; Lopez, Rassen M.; Ong, Jocelyn C. (College of Engineering, 1992)
The International Students Program (ISP) was created by the University Board of Regents to assist to foreign students in complying with the requirements set by government agencies such as the Department of Education, Culture and Sports (DECS) and Commission on Immigration and Deportation (CID). The ISP endorses and accomplishes most of these requirements (see Section 1.3.4 Functions of the System) on behalf of the foreign students - a task described by the ISP coordinator as ministerial. However, these past few years, ISP has also extended orientations on University life and Philippine culture. This nature of ISP's responsibility invariably circumscribes the office to the intricacies and difficulties of the government bureaucratic procedures. It has been, and still is being, experienced that the organization of information needed to perform ISP's services is loosely structured and in a state of not easily distinguishable order. Thus, there is a need to streamline ISP's operations given the bureaucratic procedures. The operations must be kept as simple as possible, particularly in the preparation of information for the services.